Influence of the 1988 earthquake on glacierization and relief of the Tsambagarav massif (Western Mongolia) - A. R. Agatova; R. K. Nepop; D. A. Ganyushkin; D. Otgonbayar; S. A. Griga; I. Yu. Ovchinnikov (Лëд и снег, 2022)
Early documentation of the consequences of the Tsambagarav earthquake happened on July 23, 1988 (M = 6.4) compiled by Soviet and Mongolian specialists allowed the authors, using the example of Tsambagarav (Mongolian Altai), to assess the impact of the seismic process on the reduction of mountain glaciation and topography of the trough valleys in the arid region of Central Asia. In 1988, in upper part of the Zuslan river valley, 13 days after the earthquake, the release of a fragment of one of the glaciers gave rise to an ice-rock avalanche «on an air cushion». Its deposits with a thickness of up to 30 m blocked the valley over a distance of 5 km. Analysis of space images taken in different time together with field researches revealed that as a result of the earthquake the glacier № 15 simultaneously lost 0.1 km2 of its tongue (10.4% of total area), as the whole in 1988–2015 it lost 56% of its area, whereas neighboring glaciers № 16 and 17, similar in size and the same exposure, lost significantly less – 35 and 15% of the area, respectively. Rapid shrinking of not only the glacier tongue, but also of its accumulation zone; the established deficit of ice volume in the broken off ice fragment (in comparison with initial assessment), and the abnormally long path of the avalanche made it possible to clarify the factors and mechanism of its initiation: the fall of the ice-snow ledge from the accumulation zone could lead to the rapid release of the broken ice fragment in the tongue part of the glacier. In 2004, 16 years after the avalanche, the buried ice in its deposits was still partially preserved, having completely degraded by 2019. The long time of the ice degradation process was caused by the high content (about half of the volume) of debris that armored the surface of avalanche sediments. The debris material of the avalanche repeats the relief of the underlying Pleistocene moraines, which may complicate the reconstruction of the number, scale and age of glacial events in avalanchehazardous areas. The relatively high rate of leveling of the avalanche traces and, as a consequence, the difficulties of their subsequent identification in the relief allow us to assume a greater number of avalanche releases, including seismic ones, in the recent geological past than it can be established at present in the Altai ridges.